Restraining Polysulfide with High‐Entropy Metal Nitride towards Long Cycle Life and High Capacity Li−S Batteries. Issue 23 (3rd December 2020) - Fang, Binren; Tian, Xiaolu; Wang, Te; Wang, Tao; Qu, Long; Li, Mingtao
Abstract: Lithium−sulfur (Li−S) batteries with ultrahigh theoretical specific capacity (1675 mAh g −1 ) have become a research hotpot, which focuses on the solution of shuttle effect of soluble lithium polysulfides (LIPS). Chemical immobilization of LIPS and encapsulation structure of the sulfur cathode are effective strategies to suppress the shuttle effect. Herein, high entropy metal nitride (HEMN) was prepared by mechanochemical‐assisted synthesis as an innovative anchor to restrain LIPS via the chemical bonding interaction between HEMN and LIPS. Furthermore, the composite of HEMN and S was encased by graphene (GR) through electrostatic attraction caused by opposite zeta potential, thus as the effective cathode (HEMN/S@GR) of Li−S batteries. HEMN has plentiful active metal sites which can chemically adsorb LIPS, enhancing the cycle life of Li−S batteries. Graphene can accelerate surface charge transfer of sulfur cathode to reduce the interface resistance because of its high conductivity. The initial specific capacity of HEMN/S@GR cathode is 1193 mAh g −1 and still maintains 695 mAh g −1 after 100 cycles at 0.1 C. When increased to 1.0 C, the initial specific capacity is 556 mAh g −1 and exhibits remarkable stability in long cycles. This study presents the synergetic effect of HEMN and graphene on LIPS in Li−S batteries, which introduces a new application way of high entropy materials in the field of energy storage devices. Abstract : Polysulfide anchor : A high‐entropy metal nitride (HEMN) was prepared as an innovative anchor to restrain lithium polysulfides via the chemical bonding interaction. The composite of HEMN and sulfur was encased by graphene to reduce the interface resistance. The absorptivity of HEMN and the high conductivity of graphene improves the capacity and cycle stability concurrently because of their synergistic effect.